New insights into fault activation and stress transfer between en echelon thrusts: The 2012 Emilia, Northern Italy, earthquake sequence. Issue 6 (27th June 2016) - Cheloni, D.; Giuliani, R.; D'Agostino, N.; Mattone, M.; Bonano, M.; Fornaro, G.; Lanari, R.; Reale, D.; Atzori, S.
Abstract: Here we present the results of the inversion of a new geodetic data set covering the 2012 Emilia seismic sequence and the following 1 year of postseismic deformation. Modeling of the geodetic data together with the use of a catalog of 3‐D relocated aftershocks allows us to constrain the rupture geometries and the coseismic and postseismic slip distributions for the two main events ( M w  6.1 and 6.0) of the sequence and to explore how these thrust events have interacted with each other. Dislocation modeling reveals that the first event ruptured a slip patch located in the center of the Middle Ferrara thrust with up to 1 m of reverse slip. The modeling of the second event, located about 15 km to the southwest, indicates a main patch with up to 60 cm of slip initiated in the deeper and flatter portion of the Mirandola thrust and progressively propagated postseismically toward the top section of the rupture plane, where most of the aftershocks and afterslip occurred. Our results also indicate that between the two main events, a third thrust segment was activated releasing a pulse of aseismic slip equivalent to a M w  5.8 event. Coulomb stress changes suggest that the aseismic event was likely triggered by the preceding main shock and that the aseismic slip event probably brought the second fault closer to failure. Our findings show significant correlations between static stress changes and seismicity and suggest that stress interaction between earthquakes plays a significant role among continental en echelon thrusts. Key Points: We computed a new geodetic data set covering the 2012 Emilia (Northern Italy) seismic sequence We defined the source models for the coseismic and postseismic phases of the two main events We explored how these thrust events have interacted with each other during the sequence